Ruin Falls [large type] - Milchman, Jenny (Wheeler Publishing, 2014)
Liz Daniels' husband, Paul, has decided that the family should visit the farm in western New York where he grew up. Stopping at a hotel on the way, Liz wakes to find their children, eight-year-old Reid and six-year-old Ally, gone. Blind panic slides into ice-cold terror as an Amber Alert is issued and detectives are called in. But in a sudden, gut-wrenching instant Liz realizes that it was no stranger who slipped into the room that night.